Development and validation of a French speech-in-noise self-test using synthetic voice in an adult population - Génin, Arnaud; Courtial, Jérôme; Balcon, Maxime; Puel, Jean-Luc; Venail, Frédéric; Ceccato, Jean-Charles (Frontiers in Audiology and Otology, 2024)
Background Speech-in-noise (SIN) audiometry is a valuable part of audiological diagnostics and clinical measurements, providing information on an individual's ability to understand in noise. To date, such tests have been developed with natural voice presented monaurally or binaurally (via diotic and dichotic presentation). The time required to develop such tests is often long. The use of synthetic voice would simplify the test creation process and self-testing would improve accessibility. Design Measurements were performed using an Android tablet (Samsung Galaxy Tab A7) and calibrated Bluetooth headphones (Tilde Pro C, Orosound). Normative values were first defined using natural or synthetic voice on 69 normal-hearing participants. A total of 463 participants then undertook the SIN test comprising synthetic voice and dichotic antiphasic presentation. Of these, 399 also performed the SIN test with diotic presentation. Results No significant differences in the speech reception threshold (SRT) were found between natural and synthetic voices for diotic presentations (p = 0.824, paired Student t-test) with normative values of −10.7 dB SNR (SD = 1.5 dB) and −10.4 dB SNR (SD = 1.4 dB), respectively. For the SoNoise test with synthetic voice and dichotic antiphasic presentation, the results showed a normative value of −17.5 dB SNR (SD = 1.5 dB), and a strong correlation (r = 0.797, p < 0.001) with the four-frequency pure-tone average (4f-PTA). Receiver operating curves (ROC) were then calculated: for a 4f-PTA of 20 dB hearing level (HL), the SRT was −14.5 dB SNR with a sensitivity of 84% and specificity of 89%. For a 4f-PTA of 30 dB HL, the SRT was −13.7 dB SNR with a sensitivity of 89% and specificity of 91%. For a 4f-PTA of 35 dB HL, the SRT was −13.0 dB SNR with a sensitivity of 88% and specificity of 93%. The normative binaural intelligibility level difference (BILD) value was 8.6 dB (SD = 2.0 dB) with normal-hearing participants. The learning effect due to the task and interface was 1.7 dB (1st to 7th test) and test duration was 3 min. Conclusion The SoNoise test in its synthetic dichotic antiphasic presentation is a fast and reliable tool to diagnose hearing impairment at 20, 30, and 35 dB HL cut-offs.